Variation of stand structure and regeneration of Mediterranean holm oak along a grazing intensity gradient - Cierjacks, a.; Hensen, I (Plant Ecology (formerly Vegetatio), 2004)
Mediterranean ecosystems are traditionally inﬂuenced by human disturbance. In the mountain chains of southeastern Spain, holm oak forests representing the potential natural vegetation are currently highly fragmented and subjected to extensive grazing by goats and sheep. This grazing activity by large herbivores has important impacts on community structure and dynamics of the remaining remnants because several processes associated with reproduction are affected. The present research analyses the variation of stand structure and regeneration of six forests dominated by Quercus ilex along a gradient of increasing grazing intensity. Stands of higher grazing intensity are characterized by a lower trunk number. Particularly, trees 1.3 m height and diameter classes 20 cm are clearly less represented. In addition, more intensively grazed forests show a highly aggregated dispersion of trees, which might be explained by an increase of clonally produced ramets by silvipastoral use. On the other hand, no Quercus ilex seedlings were found in any of the stands examined, although acorn production was high and did not correlate with grazing intensity. However, grazing clearly inﬂuences the quality of acorn harvest. We found a signiﬁcant negative correlation between acorn length, acorn mass and grazing intensity and a positive correlation between the percentage of aborted acorns, acorn predation and herbivore activity. Thus, management of grazing in holm oak forests must take the high inﬂuence that livestock exerts on the regeneration of Quercus ilex into account, and maximum sustainable grazing intensity should be signiﬁcantly lower than 0.8 animals per ha.
Keywords: acorn predation; acorn quality; forest conservation; grazing intensity; Quercus ilex; south-eastern spain; sustainable land-use; vegetative reproduction